CHANGING TRENDS IN FREQUENCY OF EXTENDED SPECTRUM BETA LACTAMASE PRODUCING GRAM NEGATIVE BACILLI IN INTENSIVE CARE UNITS OF A TERTIARY CARE HOSPITAL: Changing trends in Frequency of Expended Spectrum Beta Lactamase - Sattar, Abdul; Faqir, Farah; Abbasi, Shahid Ahmed; Fraz, Ali; Hussain, Zaki (Pakistan Armed Forces Medical Journal, 2009)
Objective: To determine the frequency of isolation of extended spectrum beta lactamase (ESBL) producing Gram negative bacteria from intensive care units (ICUs) of a tertiary care hospital. Study Design: Retrospective descriptive study. Place and Duration of Study: The study was carried out at the department of microbiology Army Medical College Rawalpindi from Dec 2003 to Nov 2007. Materials and Methods: This study was carried out from Dec 2003 to Nov 2007.  A total of 590 consecutive Gram-negative bacilli were recovered during the four year study period from various samples including urine, blood, pus, sputum, high vaginal swabs (HVS), ascitic fluid, central venous lines (CVP), chest tubes, catheter tips, NBL (nasobronchial lavage), CSF, tissue, endotracheal tube (ETT) tip and pleural fluid in ICUs. Extended spectrum β-lactamase detection in these isolates was carried out by Kirby- Bauer double disc synergy method. Results: The frequency of ESBL producing organisms was 84 (66%) (December 03 to November 04), 80(54%) (December 04 to November 05), 80(57%) (December 05 to November 06) and 82 (47%) (December 06 to November 07) (p